Analisa Proses Peminjaman Buku pada Perpustakaan dengan Algoritma Association Rule - Eferoni Ndruru (Yayasan Literasi Sains Indonesia, 2025)
Utilization of data in the information system to support decision-making activities, is not enough to rely on operational data alone, data analysis is needed to explore the potential of existing information. Decision makers try to utilize the existing data warehouse to explore useful information to help make decisions, This encourages the emergence of the Library is to have a fairly large collection of books ranging from textbooks to encyclopedias. Library visitors are also quite a lot. The Association Rule method is one technique for searching for data that is simultaneous in one transaction, where the book loan data in the database will be formed into one item set of up to 3 items. This library has a fairly large collection of books ranging from textbooks to encyclopedias. Library visitors are also quite a lot. Visitors who in this case are students often borrow books when there are assignments from lecturers and when they want to compile a final assignment or thesis.